Good Corporate Governance (GCG) Leverage Profitabilitas dan Nilai Perusahaan Pada BUMN Yang Melakukan Penambahan Saham Beredar - Wahyuni EDT, Risa (Politeknik Raflesia Press, 2024)
This research aims to see the influence of good corporate governance (GCG), leverage, profitability on company value. The data source used in this research is secondary data. The type of data used is quantitative data in the form of financial reports that have been uploaded to the Indonesia Stock Exchange (BEI) in 2016-2022. The objects of this research are five state-owned companies, namely PT Semen Indonesia, PT Waskita Karya, PT Adhi Karya, PT Karakatau Steel and PT Garuda Indonesia. So that samples taken using purposive sampling technique obtained a sample of 35 samples for research. The statistical method used is multiple linear regression analysis, with hypothesis testing using partial tests (t tests) and simultaneous tests (f tests). The results of research hypothesis testing show that GCG does not have a significant effect on company value, leverage has a negatif and significant effect on company value, profitability has a positive and significant effect on company value and together the variables GCG, leverage and profitability have an effect on company value